Streptomyces griseoincarnatus AR2 from the cold desert as a biofactory for secondary metabolites with multifaceted bioactivities, confirmed by in vitro and in silico approaches - Arisha Rameen Bhatti; Noor Hassan; Hazrat Ali; Noor ul Huda; Abdul Tawab; Saba Khan; Ambreen Latif; Asad Ali; Waseem Abbas; Iqra Latif Ghuman; Mohsin Khan; Aiman Umar; et al. (Archives of Microbiology, 2026)

Bacteriophage therapy for antimicrobial-resistant, biofilm‑associated diabetic foot infection: delivery routes, phage antibiotic synergy, and practical wound‑care integration - Muhammad Irbaz; Zunaira Hamood; Summayah Shahid; Afra Ghufran; Aamir Ajmal; Iqra Rafiq (Archives of Microbiology, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Interfacial construction of Co-MOF/NiCu-MOF for enhanced visible-light-driven peroxymonosulfate activation and ciprofloxacin degradation: Mechanistic insights, kinetics and stability study - Raza Ullah; Nasim Ullah; Abdul Qadir; Muzamil Ahmad; Alamgir; Muhammad Fayaz; Muhammad Rafiq; Adeel Ahmed; Muhammad Adnan; Fangqing Wang; Bing Yu; Hailin Cong (Journal of Environmental Chemical Engineering, 2026)

Advancements in the research of antioxidant peptides: A comprehensive overview - Xuelin Bai; Wei Pan; Mengyuan Xu; Muhammad Rafiq; Bing Yu; Hailin Cong (Food Research International, 2026)

Harnessing the biocontrol potential of Trichoderma: Mechanisms, applications, and future prospects in sustainable crop protection - Muhammad Faiq Irfan; Amjad Ali; Rabia Noor; Aniqa Ijaz; Hamza Rafiq; Faisal Shafiq Mirza (Physiological and Molecular Plant Pathology, 2026)

The role of Campylobacter group II phages in mitigating Campylobacter contamination across the poultry food chain: Current applications and future prospects - Muhammad Shahzad Rafiq; Syed Sami Haider; Ziyi Li; Muhammad Sarmad; Dongxin Ma; Muhammad Ali Khan; Junhao Wang; Shuaifeng Gu; Pan Tao; Muhammad Tanweer Khan; Haihong Hao (Food Research International, 2026)

Botulinum toxin from foodborne hazard to aesthetic and biomedical tool: mechanisms, applications, detection strategies, and future perspectives - Muhammad Adnan; Muhammad Waqar; Rais Ahmed; Haroon Afzal; Muhammad Abdullah Mueen; Urooj Qayyum; Farhang Hameed Awlqadr; Muhammad Talha Yaqoob; Sabrin R. M. Ibrahim; Gamal A. Mohamed; Iqra Rafiq; Hagar M. Mohamed (Archives of Microbiology, 2026)

Entropy generation in electroosmotic cilia-induced Jeffrey fluid flow through an axisymmetric tube with slip effects - Muhammad Yousuf Rafiq; Zaheer Abbas; Hafiz Shahzad; Sharia Bashir (Dynamics of Atmospheres and Oceans, 2026)

Engineering hybrid hydrogels from sticker–spacer peptide and molybdenum disulfide (MoS2) for advanced antimicrobial therapy - Muhammad Younis; Farhat Rafiq; Shuo Jin; Mussarat Tasleem; Muhammad Saleem; Yongchang Tian; Li Chen; Mohammad Aslam; Dalaver H. Anjum; Jabir Ubaid; Rehan Umer; Xiaofei Chen; et al. (Chemical Engineering Journal, 2026)

Disaster management technology and approaches: a focus on heterogeneous systems - Muhammad Haris; Sajjad Keshtkar; Adeel Anjum; Madiha Haider Syed; Hirohisa Kojima; Rafiq Ahmad (Environment Systems and Decisions, 2026)

Nano zero-valent iron-modified biochar regulates soil carbon mineralization and stability across aggregates in alpine degraded grassland - Yao Li; Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Feida Sun; Jinchao Gong; Shijie Zhou; Zhouwen Ma; Chengjing Wu; Lin Liu; Ran Xue; Yue Xiu; et al. (Soil Ecology Letters, 2026)

Lead and cadmium contamination in soils: impacts and phytoremediation strategies using ornamental plants, nanoparticles, and organic growth regulators - Sumbal Ammara; Muhammad Tariq Rafiq; Basharat Ali; Rukhsanda Aziz; Maria Aziz (Environmental Monitoring and Assessment, 2026)

Experimental analysis on the efficacy of water-based mud containing modified graphene nanoplatelets in transporting sand particles through concentric and eccentric drill pipes - Muftahu Nuhu Yahya; Muhammad Nurul Anam Bin Mohd Norddin; Azad Anugerah Ali Rasol; Jeffrey Oseh; Muhammad Muhammad; Ahmed Rafiq Albajalan (Arabian Journal of Geosciences, 2026)
Traditional drilling muds frequently have trouble efficiently transporting cuttings to the surface, which impedes drilling efficiency and progress. The possibility of a nano addition to enhance the cutting transport capability of water-based muds (WBM) is examined in this work. This study employed graphene nanoplatelets (GNPs)-based drilling muds made from rice husk waste and modified with Triton-X100 to determine how sandstone particles are removed from vertical and deviated pipelines at 0 o , 50 o , 55 o , and 60 o . This study primarily focused on how the mud velocity of modified GNPs (GR-T) and unmodified GNPs (GR) at 0.125, 0.25, and 0.375wt.% concentrations affected WBM cutting transport efficiency (CTE). To solve this problem, a tailor-made flow loop was constructed to simulate vertical and deviated well conditions at 0.6, 0.8, and 1.0 L/s mud flowrates. Furthermore, sandstone particles from 1.40 to 2.00 mm were selected to replicate drilled cuttings at varied pipe eccentricities (e = -1, 0, and + 1). The results show that GR-T concentrations are more stable and effective than GR concentrations at improving rheology, filtration, and removal of sandstone particles in the WBM system. In all experiments, the vertical (0°) pipe angle is easiest to clean, whereas the 55° angle is hardest. An eccentric drill pipe (e = + 1) cleaned the solid particles the most. The CTE of the GR-T mud system was 52% at e = -1, 55% at e = 0, and 57% at e = + 1 at a hole angle of 55◦. The removal of cuttings was facilitated at higher mud flow rates, as the increased agitation enhanced mud velocity, altered the conveyance of cuttings within the downstream flow, promoted their transition to the upstream flow, and consequently inhibited the development of a cuttings bed. Due to lesser mud velocity, removal of bedding formation was less effective at lower flowrates. The study found that higher mud rheology and flowrates erode sandstone particles the most. Additionally, the examined GR-T induced sufficient mud velocity to significantly influence the positive eccentric annulus, which improved the WBM cutting transport capacity and expedited deviated wellbore drilling.

Impacts of climate change and local stressors on the coral community structure off the eastern coast of Pakistan - Amjad Ali; Azka Rafiq Malik; Naveed Ahmad; Gulab Said; Zulfiqar Ali Mirani; Seema Shafique; Habibul Hassan; Ateeque Rahman Khooharo; Faiz Muhammad (Regional Studies in Marine Science, 2026)

Synergistic antifungal action of chitosan‑zinc oxide nanocomposite against sclerotial-forming phytopathogenic fungus Sclerotium rolfsii - Muhammad Jarrar Ahmed; Amna Shoaib; Muhammad Rafiq (Pesticide Biochemistry and Physiology, 2026)

Molecular mechanisms of heavy metal uptake, accumulation, and tolerance in sweet potato (Ipomoea batatas): implications for phytoremediation and food safety - Muhammad Shahid; Muhammad Mohsin Altaf; Muhammad Ahsan Altaf; Rafiq Ahmad; Kashif Khan; Cheng-cheng Si (Plant and Soil, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Nonlinear analysis of thermo-magneto slip flow of Jeffery fluid in a wavy curved channel - Maham Mujahid; Mounirah Areshi; Zaheer Abbas; Muhammad Yousuf Rafiq; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Large-animal farmers’ knowledge, attitudes, and practices regarding antibiotic usage in dairy and beef fattening farms in Bangladesh’s milk pocket areas - Fardina Sultana Sumi; Kazi Rafiq; A. K. M. Anisur Rahman; Muhammad Tofazzal Hossain; Purba Islam; Md. Rakib Hasan; Shah Md. Iqbal; Anan Binte Zaman (Tropical Animal Health and Production, 2026)

Evaluation of Genetic Diversity, Yield, and Its Associated Traits in Rice (Oryza Sativa L.) Genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Abdul Rehman; Shabir Ahmad; Khairiah Mubarak Alwutayd; Fatmah Ahmed Safhi; Javed Iqbal; Rashid Iqbal (Plant Molecular Biology Reporter, 2026)

Health risk evaluation of toxic metals in food crops irrigated with wastewater of Hattar Industrial Estate, Pakistan: a simulated gastrointestinal model approach - Ummama Khan; Rukhsanda Aziz; Muhammad Arshad; Basharat Ali; Muhammad Suhaib; Muhammad Tariq Rafiq (Environmental Monitoring and Assessment, 2026)

Modeling the interplay of cultivars, irrigation regimes, and planting dates for optimizing cotton productivity in core and non-core cotton areas of Pakistan - Raheel Osman; Muhammad Shahid Iqbal; Zareen Sarfraz; Abid Mahmood; Muhammad Rafiq Shahid; Til Feike; Lin Wang; Shenglei Fu; Syed Tahir Ata-Ul-Karim (Computers and Electronics in Agriculture, 2026)

Intraspecific and interspecific variation of Salvadora species (S. oleoides Decne. and S. persica L.) along an aridity gradient in dryland ecosystems - Ummar Iqbal; Atta Hussain Sahir; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Trees, 2026)

Microstructural adaptations of snow bush (Aerva javanica (Burm.f.) Juss. Ex Schult.) in desert ecosystems - Sana Abid; Ummar Iqbal; Muhammad Sharif; Sadaf Rafiq; Aisha Sana; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (The Science of Nature, 2026)

Fluctuations in Ecosystem Services in Response to Land Conversion and Climate Extremes as an Index of Ecosystem Degradation and Restoration: A Comparison of the Lake Chad and Aral Sea Basins - Emeka Edwin Igboeli; Chukwuka Prince Ogbue; Friday Uchenna Ochege; Muhammad Afzal; Rafiq Hamdi; Albert Poponi Maniraho; Geping Luo (Ecosystems, 2026)

(Im)mobilization of iron, manganese, and arsenic during managed aquifer recharge in Bangladesh: Push-pull tests under oxidative and reductive conditions - Muhammad Risalat Rafiq; Emiel Kruisdijk; Kazi Matin Ahmed; Louis C. Rietveld; Boris M. van Breukelen (Water Research, 2026)

Effects of land use type on soil aggregate stability and organic carbon fractions in the He Huang Valley, Qinghai-Tibet plateau - Anum Rafiq; Zhaolong Zhu; Nicholas T. Girkin; Yubin Wang; Zubaira Maqbool; Muhammad Laeeq Ur Rehman Hashmi; Muhammad Azeem; Shaoshan An (Applied Soil Ecology, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Biochar-derived dissolved organic matter induced changes in the bacterial communities structure and metabolic functions in As and Cd contaminated soil - Muhammad Azeem; Ruixia Han; Siyao Liu; Kubwimana J. Jacques; Hamada Abdelrahman; Syed S.H. Kazmi; Abdul Kareem; Zulqarnain H. Khan; Nazia Rafiq; Hui Li; Yakov Kuzyakov; Kun Qin (Environmental Research, 2025)

Green approaches for modifying lignocellulosic features: Recent advances in reducing recalcitrance for sustainable bioethanol production - Muhammad Adnan; Adeel Ahmed; Muhammad Rafiq; Nasim Ullah; Ali Ahmad; Muhammad Sarfraz; Raza Ullah; Muzamil Ahmad; Bing Yu; Hailin Cong (Biomass and Bioenergy, 2025)

Phenotypic Characterization and Adaptability of Wild Sugarcane to Diverse Pedospheric and Atmospheric Conditions - Ummar Iqbal; Mehboob Ahmad; Muhammad Sharif; Abdul Wahab; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Tropical Plant Biology, 2025)

Dissecting Genetic Variability and Combining Ability for Salt Tolerance in Rice Based on Morpho-Physiological Traits - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq (Journal of Crop Health, 2025)

Panel data insights into adoption of green technology and its economic role in shaping sustainability goals - Bin Xu; Ata Al Shraah; Siao-Yun Wei; Ali Mohsin Ba Awain; Muhammad Rafiq; Shamim Akhter; Tazeem Shahbaz (Clean Technologies and Environmental Policy, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

Retraction notice to “Recent advancement challenges with synthesis of biocompatible hemodialysis membranes” [Chemosphere 307, November 2022, 135626] - Shafiq Uz Zaman; Sikander Rafiq; Abulhassan Ali; Muhammad Shozab Mehdi; Amber Arshad; Saif-ur Rehman; Nawshad Muhammad; Muhammad Irfan; Muhammad Shahzad Khurram; Muhammad Khaliq U. Zaman; Abdulkader S. Hanbazazah; Hooi Ren Lim; et al. (Chemosphere, 2025)

From scorching sands to survival: adaptive tale of the genus Tribulus (T. longipetalus, T. terrestris and T. pentandrus) in desert ecosystem - Ummar Iqbal; Muhammad Sharif; Sana Abid; Sadaf Rafiq; Abdul Wahab (The Science of Nature, 2025)

Balancing Nitrogen Application to Enhance Soil Health and Mitigate Heavy Metal Contamination Risks in Sweet Potato Cultivation - Rafiq Ahmad; Cheng-cheng Si; Shah Fahad; Wajid Ali Khattak; Muhammad Zakir (Journal of Soil Science and Plant Nutrition, 2025)

Bacterial programmed cell death and toxin-antitoxin system in bacteria - Iqra Rafiq; Mudassar Mohiuddin; Muhammad Waqar (Archives of Microbiology, 2025)

Hollow cavity engineering of MOF-derived hierarchical nitrogen-doped In2O3@carbon for efficient photocatalytic degradation of tetracycline hydrochloride - Raza Ullah; Muhammad Rafiq; Alamgir; Abdul Qadir; Adeel Ahmed; Muhammad Fayaz; Muhammad Adnan; Nasim Ullah; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Intensifying the charge transfer on N–(CxNx+1) catalysts system: A cutting–edge approach for sunlight driven hydrogen production† - Ejaz Hussain; Muhammad Jalil; Javeria Mansab; Muhammad Zeeshan Abid; Shahid Iqbal; Abeer Hashem; Amal M. Al-Mohaimeed; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Synergistic performance of silver/polyacrylic acid doped ZrO2 nanostructures for dye degradation and bactericidal behavior with molecular docking analysis - Muhammad Ikram; Alvina Rafiq Butt; Sidra Bano; Sadia Naz; Sawaira Moeen; Anwar Ul-Hamid; Ali Haider; Amel Ayari-Akkari (Environment, Development and Sustainability, 2025)

Structural Traits Driving Water Hyacinth (Eichhornia crassipes) Aggressive Spread and Ecosystem Disruption - Ummar Iqbal; Abdul Wahab; Sadaf Rafiq; Sibgha Noreen; Sana Abid; Muhammad Sharif; Mehboob Ahmad; Muhammad Yousuf (Water, Air, & Soil Pollution, 2025)

Turn-On-Fluorescence Sensor and Solid Sensory Chip for Cyanide Detection - Muhammad Zahid; Nadeem Raza; Samuel Bonne; Mostafa E. Salem; Negin G. Niksirat; Muhammad Zeshan; Muhammad Rafiq; Jian Zhang; Muhammad Saleem (Journal of Fluorescence, 2025)

Synthesis and effects of zinc-chitosan complex on morpho-growth and biochemical responses in Alternaria alternata, a cause of leaf blights and spots on plants - Ghulam Roquyya; Amna Shoaib; Shagufta Parveen; Muhammad Rafiq (World Journal of Microbiology and Biotechnology, 2025)

Dynamics of bi-susceptibility patterns in Covid-19 outbreaks and associated abstain strategies - Waheed Ahmad; Muhammad Rafiq; Azhar Iqbal Kashif Butt; Momina Zainab; Naeed Ahmad (Modeling Earth Systems and Environment, 2025)

Heavy Metal Uptake by Spirogyra splendida and Spirogyra circumlineata: A Sustainable Approach to Industrial Wastewater Remediation - Sadam Khan; Yuanren Jiang; Siqi Shen; Muhammad Riaz; Muhammad Tariq; Zhenxin Li; Rafiq Ahmad; Sidra Sohail; Nazim Hassan (Water, Air, & Soil Pollution, 2025)

Investigation of diabetes mellitus transmission in humans by using time delay tool and numerical treatment approach - Ali Raza; Ayesha Shabbir; Umar Shafique; Nauman Ahmed; Muhammad Rafiq (Modeling Earth Systems and Environment, 2025)

Ochrobactrum ciceri and zinc synergy combatting Fusarium verticillioides - Shagufta Perveen; Amna Shoaib; Hafiza Sibgha Yaqoob; Ghanwa Riaz; Muhammad Rafiq (Physiological and Molecular Plant Pathology, 2025)

In vitro, in silico anti-tyrosinase and anti-inflammatory activity elucidation of chrysophanol isolated from Platycladus orientalis (L.) Franco - Muhammad Rafiq; Abdul-Rehman Phull; Mubashir Hassan; Abdul Majid; Song-Ja Kim (Next Research, 2025)

Highly efficient degradation of norfloxacin by using Co3O4-CeO2 as a heterogeneous catalyst through peroxymonosulfate activation: Characterization, catalytic performance and mechanism - Muhammad Rafiq; Raza Ullah; Adeel Ahmed; Xin Liu; Muhammad Usman; Qinghua Cao; Muhammad Adnan; Muhammad Fayaz; Waqas Haider; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Thriving in extremes: Adaptability potential of desert cotton Aerva javanica to hyper-arid saline conditions - Ummar Iqbal; Sana Abid; Muhammad Sharif; Sadaf Rafiq; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (Journal of Arid Environments, 2025)

Synergistic induction of immunogenic cell death by icaritin, JQ1, and doxorubicin to enhance immunotherapy in hepatocellular carcinoma - Wei Pan; Fengyuan Gao; Huinan Wang; Yuanyuan Guo; Muhammad Rafiq; Hailin Cong; Youqing Shen; Bing Yu (Chemical Engineering Journal, 2025)

Phytoremediation Capacity of Saltwort (Salsola imbricata Forssk.) Determined by Tissue Organization and Physio-biochemical traits under Arid Saline Environments - Ummar Iqbal; Muhammad Sharjeel Arif; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Water, Air, & Soil Pollution, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Isolation and characterization of ureolytic calcifying bacteria from methane hydrate-bearing marine sediments for bio-cementation application - Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Muhammad Afzal; Zheng Su; Liu Lihua (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Catalytic charge synergy on Ni/Sr@rTiO2 system to promote hydrogen evolution for the implementation of green energy technologies - Ejaz Hussain; Sidra Khan; Muhammad Jalil; Muhammad Zeeshan Abid; Abdul Rauf; Nagina Naveed Riaz; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Disease resistance to tomato yellow leaf curl virus (TYLCV) enhanced by natural plant growth regulators and biopesticide - Sajid Mehmood; Marina Sajid; Tamsal Murtaza; Tanveer Hussain; Rana Naveed Ur Rehman; Muhammad Tahir Akram; Huma Abbas; Khadija Rafiq; Muhammad Kamran; Manzoor Hussain; Muhammad Inam ul Haq; Gull-e-laala Khan (Journal of Plant Diseases and Protection, 2025)

Genetic Divergence Among Sorghum (Sorghum bicolor L.) Genotypes Grown Under Rainfed Conditions - Rafiq Ahmad; Ghulam Shabbir; Syed Farman Ullah; Danish Ibrar; Muhammad Ilyas; Esam M. Al-Shaebi; Yawen Zeng; Abdul Qayyum (Journal of Crop Health, 2025)

Innovative use of ceramic waste in cement grout for sustainable semi-flexible pavement solutions - Rania Al-Nawasir; Basim Al-Humeidawi; Muhammad Imran Khan; Rafiq M. Choudhry; Mohammad Iqbal Malik; M. S. Abo Dhaheer (Innovative Infrastructure Solutions, 2025)

Effects of Tribulus terrestris extract and 17 α-methyl testosterone on masculinization, growth, economic efficiency and health assessment of Nile tilapia (Oreochromis niloticus) - Habib Ul Hassan; Amjad Ali; Basim S. A. Al Sulivany; Muhammad Kabir; Roohi Kanwal; Mohammad Z. Ahmed; Rizwana Abdul Ghaffar; Meer Zeeshan Ijaz; Naseem Rafiq; Mary Mahwish; Mohammad Abdul Momin Siddique (Aquaculture International, 2025)

Unveiling the surface potential and selectivity of Ti3C2Tx/rGO adsorbents for arsenic removal from water system - Muhammad Zeeshan Abid; Khezina Rafiq; Aqsa Khan Buzdar; Muhammad Zaryab Waleed; Ejaz Hussain (Journal of Cleaner Production, 2025)

Maackiain: A comprehensive review of its pharmacology, synthesis, pharmacokinetics and toxicity - Waqas Haider; Wei Pan; Dayang Wang; Waqas Niaz; Muhammad Kashif Zaman; Raza Ullah; Shakir Ullah; Muhammad Rafiq; Bing Yu; Hailin Cong (Chemico-Biological Interactions, 2025)

Correction: Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Investigating the effects of a single ASPM variant (c.8508_8509) on brain architecture among siblings in a consanguineous Pakistani family - Komal Aslam; Aysha Saeed; Iffat Jamil; Hafiza Iqra Saeed; Ramisha Khan; Samina Hassan; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; Rasheeda Bashir; Muhammad Sajid Hussain; Shahid Mahmood Baig; et al. (Molecular Biology Reports, 2024)

Diagnostic and therapeutic value of EVs in lungs diseases and inflammation - Ali Afzal; Muhammad Babar Khawar; Ume Habiba; Hanan Afzal; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Rimsha Abaidullah; Zoya Asif; Tahaa Saeed (Molecular Biology Reports, 2024)

Real-time expression and in silico characterization of pea genes involved in salt and water-deficit stress - Muhammad Farooq; Rafiq Ahmad; Muhammad Shahzad; Saad Ur Rehman; Yasar Sajjad; Amjad Hassan; Mohammad Maroof Shah; Amber Afroz; Sabaz Ali Khan (Molecular Biology Reports, 2024)

Correction to: Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Vanillic Acid Enhances Mung Bean Resistance and Growth Against Macrophomina phaseolina as a Sustainable Antifungal Approach - Numan Ali; Amna Shoaib; Muhammad Rafiq; Barizah Malik; Muhammad Yousaf (Journal of Crop Health, 2024)

Evaluation of morphological and biochemical variations in peas under two widespread abiotic stresses - Muhammad Farooq; Rafiq Ahmad; Muhammad Shahzad; Khalid Ahmad; Yasar Sajjad; Amjad Hassan; Abdul Nazir; Mohammad Maroof Shah; Bibi Kalsoom; Sabaz Ali Khan (Acta Physiologiae Plantarum, 2024)

Enhanced activation of peroxymonosulfate by nanomagnetic CoFe2O4-CeO2/g-C3N4 composites as a heterogeneous catalyst for metronidazole degradation - Adeel Ahmed; Muhammad Usman; Muhammad Rafiq; Muhammad Adnan; Raza Ullah; Hailin Cong; Bing Yu (Journal of Water Process Engineering, 2024)

A cutting–edge approach to remove arsenic contents from ground water via sulfur doped copper ferrites (S–CuFe2O4) † - Ejaz Hussain; Aqsa Khan Buzdar; Muhammad Zeeshan Abid; Abdul Rauf; Khezina Rafiq (Journal of Environmental Management, 2024)

Team GHRM and Team Pro-environmental behavior - Muhammad Farrukh; Ali Raza; Muhammad Rafiq; Nabeel Ansari (Environment, Development and Sustainability, 2024)

Salvianolic acid B improves mitochondrial dysfunction of septic cardiomyopathy via enhancing ATF5-mediated mitochondrial unfolded protein response - Renshan Chen; Anran Zheng; Yunjing Wang; Liyou Guo; Huaqian Dou; Liangyan Lu; Muhammad Rafiq; Peihua Li; Xiuhui Chen; Qing Xiao (Toxicology and Applied Pharmacology, 2024)

Mn-MOF derived N-doped MnOx@carbon heterogeneous catalysts for Vis-light, S2O82, HSO5, Vis/S2O82, and Vis/HSO5-induced degradation of metronidazole: Kinetics and mechanistic study - Raza Ullah; Muhammad Rafiq; Alamgir; Adeel Ahmed; Xin Liu; Waqas Haider; Muhammad Fayaz; Qinghua Cao; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2024)

Mathematical modeling of Ebola using delay differential equations - Ali Raza; Nauman Ahmed; Muhammad Rafiq; Ali Akgül; Alicia Cordero; Juan R. Torregrosa (Modeling Earth Systems and Environment, 2024)
Nonlinear delay differential equations (NDDEs) are essential in mathematical epidemiology, computational mathematics, sciences, etc. In this research paper, we have presented a delayed mathematical model of the Ebola virus to analyze its transmission dynamics in the human population. The delayed Ebola model is based on the four human compartments susceptible, exposed, infected, and recovered (SEIR). A time-delayed technique is used to slow down the dynamics of the host population. Two significant stages are analyzed in the said model: Ebola-free equilibrium (EFE) and Ebola-existing equilibrium (EEE). Also, the reproduction number of a model with the sensitivity of parameters is studied. Furthermore, the local asymptotical stability (LAS) and global asymptotical stability (GAS) around the two stages are studied rigorously using the Jacobian matrix Routh–Hurwitz criterion strategies for stability and Lyapunov function stability. The delay effect has been observed in the model in inverse relation of susceptible and infected humans (it means the increase of delay tactics that the susceptibility of humans increases and the infectivity of humans decreases eventually approaches zero which means that Ebola has been controlled into the population). For the numerical results, the Euler method is designed for the system of delay differential equations (DDEs) to verify the results with an analytical model analysis.

Genetic testing perspectives in Pakistani population: a survey on knowledge, attitudes, awareness, and concerns - Mohammad Uzair; Rida Fatima; Shafia Rafiq; Maimoona Jabeen; Hammad Qaiser; Muhammad Arshad; Shahid Bashir (Journal of Community Genetics, 2024)

Salt-Tolerant Plant Growth-Promoting Bacteria (ST-PGPB): An Effective Strategy for Sustainable Food Production - Syeda Tahseen Zahra; Mohsin Tariq; Muhammad Abdullah; Muhammad Kaleem Ullah; Abdul Rafay Rafiq; Aisha Siddique; Muhammad Shafiq Shahid; Temoor Ahmed; Imrana Jamil (Current Microbiology, 2024)

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

Unraveling the role of natural functional oils in modulating osteoarthritis related complications - Muhammad Asim Shabbir; Fakiha Mehak; Moazzam Rafiq Khan; Waqar Ahmed; Muhammad Furqan Nawaz; Abdo Hassoun; Zuhaib F. Bhat; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Integrated study for assessing groundwater dynamics of the Dehdan village, Haripur Basin, Pakistan - Umair Bin Nisar; Siddique Akhtar Ehsan; Muhammad Imran Rafiq; Muhammad Rizwan Mughal (Journal of Applied Geophysics, 2024)

Recent Development on Sensing Strategies for Small Molecules Detections - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Anser Ali; Hussain Raza; Song Ja Kim; Changrui Lu (Journal of Fluorescence, 2024)

Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Unveiling the impact of textile materials to prevent viral infections: Urgency for awareness and public safety† - Muhammad Zaryab Waleed; Khezina Rafiq; Muhammad Zeeshan Abid; Muhammad Burhan; Raed H. Althomali; Shahid Iqbal; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2024)

Recent synthetic approaches towards thienothiophenes: a potential template for biologically active compounds - Ayesha Rafiq; Sana Aslam; Matloob Ahmad; Muhammad Shahid Nazir; Ambar Farooq; Sadia Sultan (Molecular Diversity, 2024)

γ-Glutamyltranspeptidase (GGT) Sensitive Fluorescence Probes for Cancer Diagnosis; Brief Review - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Hussain Raza; Kim Song Ja; Changrui Lu (Journal of Fluorescence, 2024)

Bacteria populating freshly appeared supraglacial lake possess metals and antibiotic-resistant genes - Wasim Sajjad; Nikhat Ilahi; Abdul Haq; Zhanhuan Shang; Ghulam Nabi; Muhammad Rafiq; Ali Bahadur; Abhishek Banerjee; Shichang Kang (Environmental Research, 2024)

Sublethal impacts of Buprofezin and Pyriproxyfen on cotton mealybug Phenacoccus solenopsis through transgenerational hormesis - Sabir Hussain; Khalid Ali Khan; Muhammad Rafiq Shahid; Tooba Ather; Lal Khan; Amna Bibi; Sadia Kanwal; Nadia Hussain Ahmad; Ali Jan Bugti (Phytoparasitica, 2024)

Cryosphere: a frozen home of microbes and a potential source for drug discovery - Sahib Zada; Mohsin Khan; Zheng Su; Wasim Sajjad; Muhammad Rafiq (Archives of Microbiology, 2024)

Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Recent advances in applications of marine hydrocolloids for improving bread quality - Anum Ishaq; Muhammad Nadeem; Rafiq Ahmad; Zahoor Ahmed; Nauman Khalid (Food Hydrocolloids, 2024)

Natural esters as sustainable alternating dielectric liquids for transformer insulation system: analyzing the state of the art - Muhammad Rafiq; Muhammad Shafique; Muhammad Ateeq; Markus Zink; Deniz Targitay (Clean Technologies and Environmental Policy, 2024)

Efficient performance of InP and InP/ZnS quantum dots for photocatalytic degradation of toxic aquatic pollutants - Maryam Abbasi; Rukhsanda Aziz; Muhammad Tariq Rafiq; Aziz Ur Rahim Bacha; Zahid Ullah; Abdul Ghaffar; Ghulam Mustafa; Iqra Nabi; Malik Tahir Hayat (Environmental Science and Pollution Research, 2024)

Nickel uptake in leafy greens from contaminated soil: an investigation into phytoavailability and health risk assessment using in vitro digestion model - Sumbal Ammara; Muhammad Tariq Rafiq; Rukhsanda Aziz; Ying Feng; Sultan Mehmood; Mehwish Taneez; Muhammad Suhaib; Fatima Asif (Environmental Monitoring and Assessment, 2024)

Microbial diversity and community structure dynamics in acid mine drainage: Acidic fire with dissolved heavy metals - Wasim Sajjad; Nikhat Ilahi; Shichang Kang; Ali Bahadur; Abhishek Banerjee; Sahib Zada; Barkat Ali; Muhammad Rafiq; Guodong Zheng (Science of The Total Environment, 2024)

Patterns of bacterial communities in the rhizosphere and rhizoplane of alpine wet meadows - Awais Iqbal; Muhammad Maqsood Ur Rehman; Wasim Sajjad; Abraham Allan Degen; Muhammad Rafiq; Niu Jiahuan; Salman Khan; Zhanhuan Shang (Environmental Research, 2024)

Emerging role of lipophagy in liver disorders - Bismillah Nazeer; Muhammad Babar Khawar; Muhammad Usman Khalid; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Ahmad Ali; Hooriya Fatima; Sadia Ahmad (Molecular and Cellular Biochemistry, 2024)

Efficient heterogeneous activation of peroxymonosulfate by manganese-doped LaCoO3 perovskites for metronidazole degradation: A mechanistic study and reaction pathways - Muhammad Rafiq; Adeel Ahmed; Muhammad Usman; Raza Ullah; Fengyuan Gao; Muhammad Mateen; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Surface sensitization of TiO2 via Pd/Rb2O cocatalysts: Mechanistic insights to the arsenic elimination from ground drinking water† - Kashaf Ul Sahar; Khezina Rafiq; Muhammad Zeeshan Abid; Ubaid ur Rehman; Ujala Quyyum; Abdul Rauf; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2023)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

High prevalence of antibiotic-resistant and metal-tolerant cultivable bacteria in remote glacier environment - Wasim Sajjad; Barkat Ali; Hewen Niu; Nikhat Ilahi; Muhammad Rafiq; Ali Bahadur; Abhishek Banerjee; Shichang Kang (Environmental Research, 2023)

Industrial wastewater irrigation increased higher heavy metals uptake and expansins, metacaspases, and cystatin genes expression in Parthenium and maize - Kinza Penzy; Said Muhammad; Muhammad Shahzad; Imran Hussain; Sabaz Ali Khan; Arshad Mehmood Abbasi; Imtiaz Khan; Rafiq Ahmad (Environmental Monitoring and Assessment, 2023)

Prospects of recycling from end-of-life of Li-ion batteries on alleviating materials demand-supply gap in new electric vehicles in Asia - Muhammad Shafique; Muhammad Ateeq; Muhammad Rafiq; Anam Azam; Xiaowei Luo (Waste Management, 2023)

Thermochemical conversion of agricultural waste to hydrogen, methane, and biofuels: A review - Ahmed Khan; Muhammad Bilal Khan Niazi; Reema Ansar; Zaib Jahan; Farhan Javaid; Rafiq Ahmad; Hirra Anjum; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

Reduced graphene oxide supported CoFe2O4 composites with enhanced peroxymonosulfate activation for the removal of sulfamethoxazole: Collaboration of radical and non-radical pathways - Adeel Ahmed; Muhammad Usman; Zhijian Ji; Muhammad Rafiq; Raza Ullah; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Occurrence, source identification and ecological risk assessment of heavy metals in water and sediments of Uchalli lake – Ramsar site, Pakistan - Ayesha Aftab; Rukhsanda Aziz; Abdul Ghaffar; Muhammad Tariq Rafiq; Ying Feng; Zafeer Saqib; Muhammad Khalid Rafiq; Muhammad Akbar Awan (Environmental Pollution, 2023)

Combination of melatonin and plant growth promoting rhizobacteria improved the growth of Spinacia oleracea L. under the arsenic and cadmium stresses - Mahnoor Asif; Rafiq Ahmad; Arshid Pervez; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Shahzad; Usman Irshad; Arshad Mehmood Abbasi (Physiological and Molecular Plant Pathology, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Assessment of heavy metals and associated oxidative stress in occupationally exposed workers from Bannu and Karak Districts in Pakistan - Kaleem Khan; Muhammad Tariq Rafiq; Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Irshad; Faridullah Faridullah; Muhammad Younas; Muhammad Daud Khan; Rukhsanda Aziz; Muhammad Amin; Awais Arifeen; Sohaib Aslam; et al. (Environmental Geochemistry and Health, 2023)

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

Prevalence and abundance of antibiotic-resistant genes in culturable bacteria inhabiting a non-polar passu glacier, karakorum mountains range, Pakistan - Sabir Nawaz; Muhammad Rafiq; Ian L. Pepper; Walter Q. Betancourt; Aamer Ali Shah; Fariha Hasan (World Journal of Microbiology and Biotechnology, 2023)

Staphylococcus Sciuri SAT-17 Facilitated in Vitro Regenerated Sugarcane Plantlets Cultivation in Saline Soil by Harmonizing Oxidative Signaling, Photosynthetic Efficiency and Nutrients Uptake Patterns - Raheel Parvez Abbasi; Muhammad Sohail Akram; Khadija Rafiq; Saadia Basheer; Naeem Iqbal (Journal of Soil Science and Plant Nutrition, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Natural remedies for Alzheimer’s disease: A systematic review of randomized controlled trials - Saara Ahmad; Saad Bilal Ahmed; Asra Khan; Muhammad Wasim; Saiqa Tabassum; Saida Haider; Fatima Ahmed; Zehra Batool; Saima Khaliq; Hamna Rafiq; Prashant Tikmani; Anwar-ul-Hassan Gilani (Metabolic Brain Disease, 2023)

Synthesis, Characterization, Optical Properties, Molecular Modeling and Urease Inhibition Analysis of Organic Ligands and Their Metal Complexes - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Mubashir Hassan; Tehreem Tahir (Journal of Fluorescence, 2023)

Moisture- and period-dependent interactive effects of plant growth-promoting rhizobacteria and AM fungus on water use and yield formation in dryland wheat - Muhammad Maqsood Ur Rehman; Ying Zhu; Muhammad Abrar; Wasim Khan; Wei Wang; Awais Iqbal; Anum Khan; Yuan Chen; Muhammad Rafiq; Muhammad Aammar Tufail; Jian-Sheng Ye; You-Cai Xiong (Plant and Soil, 2022)

How do farmers cope with climate change? An analysis of alternative adaptation strategies in drought-hit areas of Khyber Pakhtunkhwa—Pakistan - Imtiaz Alam Khan; Muhammad Rafiq; Sanaullah Panezai; Shahab E. Saqib; Raza Ullah; Muhammad Atiq (Natural Hazards, 2022)

Microplastic pollution in the surface water and sediments from Kallar Kahar wetland, Pakistan: occurrence, distribution, and characterization by ATR-FTIR - Aqsa Dilshad; Mehwish Taneez; Farhan Younas; Asma Jabeen; Muhammad Tariq Rafiq; Hina Fatimah (Environmental Monitoring and Assessment, 2022)

Prospect of Anterior Gradient 2 homodimer inhibition via repurposing FDA-approved drugs using structure-based virtual screening - Shafi Ullah; Shafi Ullah Khan; Abbas Khan; Muhammad Junaid; Humaira Rafiq; Thet Thet Htar; Yaxue Zhao; Syed Adnan Ali Shah; Abdul Wadood (Molecular Diversity, 2022)

Influences of Long-term Crop Cultivation and Fertilizer Management on Soil Aggregates Stability and Fertility in the Loess Plateau, Northern China - Farhat Ullah Khan; Adnan Anwar Khan; Kai Li; Xuexuan Xu; Muhammad Adnan; Shah Fahad; Rafiq Ahmad; Mushtaq Ahmad Khan; Taufiq Nawaz; Faisal Zaman (Journal of Soil Science and Plant Nutrition, 2022)

Use of Eudragit RS PO, HPMC K100M, Ethyl Cellulose, and Their Combination for Controlling Nicorandil Release from the Bilayer Tablets with Atorvastatin as an Immediate-Release Layer - Wajiha Iffat; Muhammad Harris Shoaib; Rabia Ismail Yousuf; Faaiza Qazi; Zafar Alam Mahmood; Iyad Naeem Muhammad; Kamran Ahmed; Farrukh Rafiq Ahmed; Muhammad Suleman Imtiaz (Journal of Pharmaceutical Innovation, 2022)

Phosphate solubilizing epilithic and endolithic bacteria isolated from clastic sedimentary rocks, Murree lower Himalaya, Pakistan - Imran Khan; Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Sumayya Zaman; Fariha Hasan (Archives of Microbiology, 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

Spatial and temporal fluctuation of rainfall and drought in Balochistan province, Pakistan - Muhammad Rafiq; Yue Cong Li; Yanpei Cheng; Ghani Rahman; Ikram Ullah; Ahmad Ali (Arabian Journal of Geosciences, 2022)

Assessment of Hg accumulation in fish and scalp hair in fishing communities along river Swat, Pakistan - Muhammad Aamir Munir; Bushra Khan; Ishaq Ahmed Mian; Muhammad Rafiq; Samreen Shahzadi; Kashif Naeem; Iqbal Ahmad (Environmental Science and Pollution Research, 2021)

Correction to: Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

Biomechanical analysis of three different types of fixators for anterior cruciate ligament reconstruction via finite element method: a patient-specific study - Nur Afikah Zainal Abidin; Abdul Hadi Abdul Wahab; Rabiatul Adibah Abdul Rahim; Mohammed Rafiq Abdul Kadir; Muhammad Hanif Ramlee (Medical & Biological Engineering & Computing, 2021)

Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

Non-obstructive monitoring of muscle fatigue for low intensity dynamic exercise with infrared thermography technique - Muhammad Faiz Md Shakhih; Nursyazana Ridzuan; Asnida Abdul Wahab; Nurul Farha Zainuddin; Laila Fadhillah Ulta Delestri; Anis Suzziani Rosslan; Mohammed Rafiq Abdul Kadir (Medical & Biological Engineering & Computing, 2021)

Wind speed pattern data and wind energy potential in Pakistan: current status, challenging platforms and innovative prospects - Hammad Saulat; Muhammad Masood Khan; Muhammad Aslam; Muhammad Chawla; Sikander Rafiq; Faisal Zafar; Muhammad Mahmood Khan; Awais Bokhari; Farrukh Jamil; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2021)

A spatial-temporal decomposition of carbon emission intensity: a sectoral level analysis in Pakistan - Muhammad Azam; Saima Nawaz; Zubair Rafiq; Nasir Iqbal (Environmental Science and Pollution Research, 2021)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

Risk assessment of hazardous elements in wastewater irrigated soil and cultivated vegetables in Pakistan - Alia Naz; Sardar Khan; Said Muhammad; Rafiq Ahmad; Salma Khalid; Abdullah Khan; Rashid Nazir; Sadia Alam; Zia ur Rahman (Arabian Journal of Geosciences, 2020)

Gene expression of thrombomodulin, TNF-α and NF-KB in coronary artery disease patients of Pakistan - Muhammad Rafiq; Afrose Liaquat; Nadia Saeed; Ghassan Umair Shamshad; Sana Mumtaz; Muhammad Jawad Khan (Molecular Biology Reports, 2020)

Soil fungal taxonomic diversity along an elevation gradient on the semi-arid Xinglong Mountain, Northwest China - Salman Khan; Ning Chen; Cankun Zhang; Luning Wang; Chun Han; Kanglong Lu; Yage Li; Muhammad Rafiq; Awais Iqbal; Changming Zhao (Archives of Microbiology, 2020)

Enhancement of salt tolerance in maize (Zea mays L.) using locally isolated Bacillus sp. SR-2-1/1 - Khadija Rafiq; Muhammad Sohail Akram; Muhammad Shahid; Uzma Qaisar; Naeem Rashid (Biologia, 2020)

Pigment production by cold-adapted bacteria and fungi: colorful tale of cryosphere with wide range applications - Wasim Sajjad; Ghufranud Din; Muhammad Rafiq; Awais Iqbal; Suliman Khan; Sahib Zada; Barkat Ali; Shichang Kang (Extremophiles, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

Cell membrane fatty acid and pigment composition of the psychrotolerant cyanobacterium Nodularia spumigena CHS1 isolated from Hopar glacier, Pakistan - Noor Hassan; Alexandre M. Anesio; Muhammad Rafiq; Jens Holtvoeth; Ian Bull; Christopher J. Williamson; Fariha Hasan (Extremophiles, 2020)

Comparative effect of organic amendments on physio-biochemical traits of young and old bean leaves grown under cadmium stress: a multivariate analysis - Muhammad Shahid; Saliha Shamshad; Abu Bakar Umer Farooq; Marina Rafiq; Sana Khalid; Camille Dumat; Yongqing Zhang; Imtyaz Hussain; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Effect of poultry litter biochar on chromium (Cr) bioavailability and accumulation in spinach (Spinacia oleracea) grown in Cr-polluted soil - Adiba Khan Sehrish; Rukhsanda Aziz; Muhammad Mazhar Hussain; Muhammad Tariq Rafiq; Muhammad Rizwan; Niaz Muhammad; Muhammad Khalid Rafiq; Anum Sehar; Jalal ud Din; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2019)

Biochar for sustainable soil and environment: a comprehensive review - Niaz Muhammad; Mubashir Hussain; Waheed Ullah; Taj Ali Khan; Shafaqat Ali; Ali Akbar; Rukhsanda Aziz; Muhammad Khalid Rafiq; Robert Thomas Bachmann; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Biomechanical features of six design of the delta external fixator for treating Pilon fracture: a finite element study - Muhammad Hanif Ramlee; Mohd Ayub Sulong; Evelyn Garcia-Nieto; Daniel Angure Penaranda; Antonio Ros Felip; Mohammed Rafiq Abdul Kadir (Medical & Biological Engineering & Computing, 2018)

Synthesis of biochar from sugarcane filter-cake and its impacts on physiological performance of lettuce (Lettuce sativa) grown on cadmium contaminated soil - Anum Sehar; Rukhsanda Aziz; Muhammad Tariq Rafiq; Muhammad Mazhar Hussain; Muhammad Rizwan; Adiba Khan Sehrish; Muhammad Khalid Rafiq; Jalal ud Din; Qaiser Hussain; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2018)

Finite element analysis of the wrist in stroke patients: the effects of hand grip - Muhammad Hanif Ramlee; Gan Kok Beng; Nazri Bajuri; Mohammed Rafiq Abdul Kadir (Medical & Biological Engineering & Computing, 2018)

A comparative study to evaluate efficiency of EDTA and calcium in alleviating arsenic toxicity to germinating and young Vicia faba L. seedlings - Marina Rafiq; Muhammad Shahid; Saliha Shamshad; Sana Khalid; Nabeel Khan Niazi; Ghulam Abbas; Muhammad Farhan Saeed; Mazhar Ali; Behzad Murtaza (Journal of Soils and Sediments, 2018)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Earliness index deters Pectinophora gossypiella incidence on advanced cultivars of Bt cotton - Muhammad Rafiq Shahid; Muhammad Shakeel; Muhammad Farooq; Muhammad Shahid Arain; Chaudhary Muhammad Shahid Hanif; Haichen Yin; Muhammad Akram; Saghir Ahmad (Arthropod-Plant Interactions, 2018)

A Brief Review on Fluorescent Copper Sensor Based on Conjugated Organic Dyes - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif; Muhammad Ashraf Shaheen; Sung-Yum Seo (Journal of Fluorescence, 2018)

Wheat productivity responses in the rice-based system under different no-till techniques and nitrogen sources - Muhammad Hamid Rafiq; Riaz Ahmad; Abdul Jabbar; Hassan Munir; Muzzammil Hussain (Environmental Science and Pollution Research, 2017)

Arsenic accumulation and physiological attributes of spinach in the presence of amendments: an implication to reduce health risk - Muhammad Shahid; Marina Rafiq; Nabeel Khan Niazi; Camille Dumat; Saliha Shamshad; Sana Khalid; Irshad Bibi (Environmental Science and Pollution Research, 2017)

Effect of Ferrule Height and Post Length on Mechanical Stress and Displacement of Endodontically Treated Maxillary Central Incisor: A Finite Element Analysis - Muhammad Ikman Ishak; Aisyah Ahmad Shafi; Mohammed Rafiq Abdul Kadir; Eshamsul Sulaiman (Journal of Medical and Biological Engineering, 2017)

Impact of Dysdercus koenigii Fabricius (Hemiptera: Pyrrhcoridae) density-dependent population on agronomic and qualitative characteristics of different transgenic cotton varieties - Muhammad Rafiq Shahid; Muhammad Farooq; Muhammad Shakeel; Abid Mahmood; Muhammad Dildar Gogi (Phytoparasitica, 2017)

Number of pegs influence focal stress distributions and micromotion in glenoid implants: a finite element study - Abdul Hadi Abdul Wahab; Mohammed Rafiq Abdul Kadir; Muhammad Noor Harun; Tunku Kamarul; Ardiyansyah Syahrom (Medical & Biological Engineering & Computing, 2017)

Organic Material Based Fluorescent Sensor for Hg2+: a Brief Review on Recent Development - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif (Journal of Fluorescence, 2017)

New lipoxygenase and cholinesterase inhibitory sphingolipids from Carthamus oxyacantha - Muhammad Dilshad; Naheed Riaz; Muhammad Saleem; Nusrat Shafiq; Muhammad Ashraf; Tayaba Ismail; Hafiza Mehwish Rafiq; Abdul Jabbar (Natural Product Research, 2016)

Psychrophilic and psychrotrophic fungi: a comprehensive review - Noor Hassan; Muhammad Rafiq; Muhammad Hayat; Aamer Ali Shah; Fariha Hasan (Reviews in Environmental Science and Bio/Technology, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Baseline susceptibility and resistance stability of Earias vittella fabricius (Lepidoptera: Noctuidae) to cypermethrin, deltamethrin and spinosad - Muhammad Tahir Jan; Naeem Abbas; Sarfraz Ali Shad; Muhammad Rafiq; Mushtaq Ahmad Saleem (Phytoparasitica, 2015)

Variations of growth, nitrogen accumulation and nitrogen use efficiency among 18 willow clones under two nitrogen regimes - Weidong Yang; Zhiqiang Zhu; Fengliang Zhao; Zheli Ding; Muhammad Tariq Rafiq; Yuyan Wang; Xincheng Zhang; Xiaoe Yang (Agroforestry Systems, 2015)

Effect of Thermal Treatment on Meat Proteins with Special Reference to Heterocyclic Aromatic Amines (HAAs) - Muhammad Asim Shabbir; Ali Raza; Faqir Muhammad Anjum; Moazzam Rafiq Khan; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2015)

Identification of a homozygous splice site mutation in the dynein axonemal light chain 4 gene on 22q13.1 in a large consanguineous family from Pakistan with congenital mirror movement disorder - Iltaf Ahmed; Kirti Mittal; Taimoor I. Sheikh; Nasim Vasli; Muhammad Arshad Rafiq; Anna Mikhailov; Mehrnaz Ohadi; Huda Mahmood; Guy A. Rouleau; Attya Bhatti; Muhammad Ayub; Myriam Srour; et al. (Human Genetics, 2014)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Novel and recurrent LDLR gene mutations in Pakistani hypercholesterolemia patients - Waqas Ahmed; Muhammad Ajmal; Ahmed Sadeque; Roslyn A. Whittall; Sobia Rafiq; Wendy Putt; Athar Khawaja; Fauzia Imtiaz; Nuzhat Ahmed; Maleeha Azam; Steve E. Humphries; Raheel Qamar (Molecular Biology Reports, 2012)

A novel autosomal recessive non-syndromic hearing impairment locus (DFNB47) maps to chromosome 2p25.1-p24.3 - Muhammad Jawad Hassan; Regie Lyn P. Santos; Muhammad Arshad Rafiq; Maria H. Chahrour; Thanh L. Pham; Muhammad Wajid; Nadine Hijab; Michael Wambangco; Kwanghyuk Lee; Muhammad Ansar; Kai Yan; Wasim Ahmad; et al. (Human Genetics, 2006)